INCLUSIVE, INNOVATIVE, AND RESILIENT: SHAPING ALBANIA'S FUTURE GROWTH FRAMEWORK - Irsida Dinoshi; Ahmet Leka (Agora International Journal of Economical Sciences, 2025)
As Albania's economy continues to evolve, traditional measures like Gross Domestic Product (GDP) fail to provide a complete picture of its economic well-being and sustainability. This paper explores the need for new tools to assess and guide Albania’s economic policies, shifting the focus from simple growth metrics to a more comprehensive evaluation of economic quality. By examining key indicators such as human capital, infrastructure development, environmental sustainability, and technological innovation, this study highlights how Albania’s GDP growth has not always translated into high-quality, inclusive, or resilient development. Despite positive growth trends, challenges remain in areas like education, infrastructure, and green energy adoption. Our findings underscore the importance of balancing economic growth with long-term objectives such as reducing inequality, fostering innovation, and promoting sustainability. This paper advocates for a more integrated, multidimensional approach to economic policy, one that prioritizes investments in human capital, infrastructure, and renewable energy to ensure that Albania’s growth is both inclusive and sustainable. By adopting this broader growth framework, Albania can align its economic trajectory with global standards of resilience and prosperity, ensuring that the benefits of growth reach all segments of society.